Fractional Coins and Fractional Derivatives - J. A. Tenreiro Machado (Abstract and Applied Analysis)
This paper discusses the fundamentals of negative probabilities and fractional calculus. The historical evolution and the main mathematical concepts are discussed, and several analogies between the two apparently unrelated topics are established. Based on the new conceptual perspective, some experiments are performed shading new light into possible future progress.